Retinal Vessel Analysis (RVA) in the Context of Subarachnoid Hemorrhage - A Proof of Concept Study - Albanna, Walid (PLoS One, 2016)
BACKGROUND: Timely detection of impending delayed cerebral ischemia after subarachnoid hemorrhage (SAH) is essential to improve outcome, but poses a diagnostic challenge. Retinal vessels as an embryological part of the intracranial vasculature are easily accessible for analysis and may hold the key to a new and non-invasive monitoring technique. This investigation aims to determine the feasibility of standardized retinal vessel analysis (RVA) in the context of SAH. METHODS: In a prospective pilot study, we performed RVA in six patients awake and cooperative with SAH in the acute phase (day 2–14) and eight patients at the time of follow-up (mean 4.6±1.7months after SAH), and included 33 age-matched healthy controls. Data was acquired using a manoeuvrable Dynamic Vessel Analyzer (Imedos Systems UG, Jena) for examination of retinal vessel dimension and neurovascular coupling. RESULTS: Image quality was satisfactory in the majority of cases (93.3%). In the acute phase after SAH, retinal arteries were significantly dilated when compared to the control group (124.2±4.3MU vs 110.9±11.4MU, p<0.01), a difference that persisted to a lesser extent in the later stage of the disease (122.7±17.2MU, p<0.05). Testing for neurovascular coupling showed a trend towards impaired primary vasodilation and secondary vasoconstriction (p = 0.08, p = 0.09 resp.) initially and partial recovery at the time of follow-up, indicating a relative improvement in a time-dependent fashion. CONCLUSION: RVA is technically feasible in patients with SAH and can detect fluctuations in vessel diameter and autoregulation even in less severely affected patients. Preliminary data suggests potential for RVA as a new and non-invasive tool for advanced SAH monitoring, but clinical relevance and prognostic value will have to be determined in a larger cohort.